Coffee development strategy in the surrounding areas of Kerinci Seblat National Park (case study of Lempur Village) - Siti Hodijah; Arman Delis (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2018)
This study aimed to analyze the coffee development strategy in the surrounding areas of Kerinci Seblat National Park (KSNP). The study was conducted in Lempur Village, as one of the villages bordering KSNP. Primary data was obtained from coffee farmers and secondary data was obtained from relevant agencies. SWOT analysis was used and the data were analyzed descriptively. The study found that the main strategy in the development of coffee in Lempur Village was the expansion of the coffee marketing area. In addition to that, other strategies are needed, such as giving information about branding and guidance for independent export, promotion both through print, electronic, and social media, using better quality coffee seeds, optimizing the use of information technology to support marketing, maximizing the empowerment of farmer institutions, optimizing coffee farming management and providing training in product innovation and diversification to increase value added in production.